Groundwater remediation using Magnesium–Aluminum alloys and in situ layered doubled hydroxides - Zhang, Jingqi; Hu, Hanjun; Chao, Jingbo; Tang, Yang; Wan, Pingyu; Yuan, Qipeng; Fisher, Adrian C.; Coulon, Frederic; Hu, Qing; Yang, Xiao Jin (Elsevier, 2021)
In situ remediation of groundwater by zerovalent iron (ZVI)-based technology faces the problems of rapid passivation, fast agglomeration, limited range of pollutants and secondary contamination. Here a new concept of Magnesium–Aluminum (Mg–Al) alloys and in situ layered double hydroxides on is proposed for the degradation and removal of a wide variety of inorganic and organic pollutants from groundwater. The Mg–Al alloy provides the electrons for the chemical reduction and/or the degradation of pollutants while released Mg2+, Al3+ and OH- ions react to generate in situ LDH precipitates, incorporating other divalent and trivalent metals and oxyanions pollutants and further adsorbing the micropollutants. The Mg–Al alloy outperforms ZVI for treating acidic, synthetic groundwater samples contaminated by complex chemical mixtures of heavy metals (Cd2+, Cr6+, Cu2+, Ni2+ and Zn2+), nitrate, AsO33-, methyl blue, trichloroacetic acid and glyphosate. Specifically, the Mg–Al alloy achieves removal efficiency ≥99.7% for these multiple pollutants at concentrations ranging between 10 and 50 mg L−1 without producing any secondary contaminants. In contrast, ZVI removal efficiency did not exceed 90% and secondary contamination up to 220 mg L−1 Fe was observed. Overall, this study provides a new alternative approach to develop efficient, cost-effective and green remediation for water and groundwater.
Keywords: Groundwater remediation; Chemical degradation; Mg–Al alloy; In situ layered double hydroxides